Vacuum technology and applications - Hucknall, David J. ([S.l.] : Butterworth-Heinemann, 1991)
A comprehensive presentation of vacuum theory and practice. Features include diagrams and photographs, and working examples demonstrating the application of formulae. Such topics as total pressure measurement, residual gas analysis, and the perfomance of pumps are discussed.